Seminar Pengembangan Softskill Bagi Karyawan Cv. Three And Group Contractor & Supplier - Yahya, Yahya (Penerbit Goodwood, 2025)
Purpose: This seminar aimed to strengthen employees’ soft skills, particularly communication, teamwork, leadership, self-management, and ethics, which are essential for professional growth and organizational effectiveness. Methodology/approach: The program applied an interactive approach through presentations, discussions, case studies, and group activities to encourage participants’ active involvement and practical application of soft skills in daily work. Results/findings: The seminar improved participants’ awareness and confidence in applying soft skills at the workplace. Employees reported better understanding of collaboration, communication, and leadership, along with increased motivation to implement these abilities in professional settings. Conclutions: Soft skill training significantly supports employee performance and complements technical skills. Developing these competencies enhances adaptability, productivity, and career growth. Limitations: The evaluation relied on short-term feedback without assessing long-term behavioral change or measurable organizational outcomes. The relatively limited number of participants may reduce the generalizability of the findings. Contribution: This program contributes to the literature on human resource development by emphasizing the role of soft skills as intangible yet critical competencies. Practically, it offers organizations a reference for integrating soft skill development into training programs to improve competitiveness and sustainability.